Relationship between design management and organizational performance in Paralympic Sports Federations - Hameed Abbas, Khelood; Abbas, Rawaa Abdulameer; Sabit, Siham Hammood (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The design departments have devoted significant attention to improve organizational performance of the sports institutions, in terms of creativity, innovation, beauty, coordination, organization, and problem solving. However, there is still need to find out new ideas and designs for the administrative levels in the sports institutions. Thus, the present study was conducted to identify the relationship between design management and organizational performance. In the current study, all the heads of sports federations in the Paralympic Committee for the academic year 2020-2021 were recruited as the participants for the study. Participant selection was done using purposive sampling method. A total of 30 individuals were recruited as the participants for the study. Based on the findings of the study, the researchers concluded that a roadmap existed in the form of a strategic approach for the Paralympic Committee, in order to achieve unique expectations by developing a plan for organizational performance.